2021
DOI: 10.1098/rspb.2021.0001
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife disturbances as a source of conspecific negative density-dependent mortality in tropical trees

Abstract: Large vertebrates are rarely considered important drivers of conspecific negative density-dependent mortality (CNDD) in plants because they are generalist consumers. However, disturbances like trampling and nesting also cause plant mortality, and their impact on plant diversity depends on the spatial overlap between wildlife habitat preferences and plant species composition. We studied the impact of native wildlife on a hyperdiverse tree community in Malaysia. Pigs ( Sus scrofa ) are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
(81 reference statements)
1
25
1
Order By: Relevance
“…The rise of some megafauna in degraded forests is also a problem. High densities of wild boars in forest edges produce strong shifts in plant diversity and function ( 50 , 51 ), and their collapse due to African swine fever could be equally disruptive ( 52 ). Ecological cascades research will be especially important for this region.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of some megafauna in degraded forests is also a problem. High densities of wild boars in forest edges produce strong shifts in plant diversity and function ( 50 , 51 ), and their collapse due to African swine fever could be equally disruptive ( 52 ). Ecological cascades research will be especially important for this region.…”
Section: Discussionmentioning
confidence: 99%
“…Larger mammalian herbivores play a key role in tree seedling survival and forest regeneration. Evidence suggests that large mammals could contribute to CNDDD at seedling stages (Murphy and Comita 2021, Luskin et al 2021). However, their diversity and abundances have been widely reduced by human activities (Corlett 2007, Benítez‐López et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that CNDDD at the seed stage may be higher in disturbed study sites, because of the loss of large mammals (Supporting information). However, CNDDD at the seedling stage may be higher in pristine study sites as large mammals are the main drivers of CNDDD processes (Murphy and Comita 2021, Luskin et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations